Translation, adaptation, and validation of the Halpern Critical Thinking Assessment to Portugal: effect of disciplinary area and academic level on critical thinking - Franco, Amanda Rodrigues (2018)
Critical thinking is essential today, state higher education institutions, organizations, and society. This study aimed to translate, adapt, and assess the psychometric proprieties of the Portuguese version of Halpern Critical Thinking Assessment (Halpern, 2012), administered to 333 college students. Also, it aimed to analyze if there were differences in total scores according to disciplinary area and academic level. Data support the validity of the Portuguese version of this instrument, and indicate differences in both variables. These findings are of interest in future research conducted in Portugal, and in cross-cultural studies using this test to assess college students' critical thinking. Seeing that critical thinking combines the skill and will that are needed for good thinking, and that, alongside benefits in academic and work contexts, a higher quality of critical thinking is expected to be associated with less negative outcomes in everyday life, this line of research is of most relevance.